THE EFFECT OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE WITH EMPLOYEE ENGAGEMENT AS A MEDIATION VARIABLE - Muhammad Donal Mon; Robin Robin; Oparton J Tarihoran (Journal of Business Studies and Management Review, 2021)
This research aims to determine the significant influence between transformational leadership on employee performance and employee engagement as a mediating variable for employees of Certain Functional Officers Immigration Analyst under the Provincial Office of the Ministry of Law and Human Rights Kepulauan Riau. This research is a quantitative study using primary data. The population in the study amounted to 216 employees, with total sample of 163 employees who filled out a questionnaire measured by using Likert scale. To answer the research hypothesis formulation, the results of data collection were analyzed using the Partial Least Square (PLS) method and assisted by SmartPLS 3.0 software. Based on the results of the analysis using the Partial Least Square (PLS) method, it was found that two components of transformational leadership, namely idealized influence and inspirational motivation, have a positive but insignificant effect on employee performance, while the other two components intellectual stimulation and individualized consideration have no effect. And when the four components of transformational leadership (idealized influence, inspirational motivation, intellectual stimulation and individualized consideration) are mediated by the employee engagement variable, there is a strengthening of the influence of transformational leadership on employee performance.